Innovaciones campesinas en el marco de la forestería comunitaria en Centroamérica - Valverde, Jaime; Ardón, Mario; Colindres, Ibis; Elías, Silvel; Rivas, Abelardo; Zappacosta, Mario (Revista de Ciencias Ambientales, 2002)
No disponible/Not available